Faktor Pendorong dan Faktor Penarik Wisatawan Domestik Berkunjung ke Kawasan Taman Nasional Komodo di Era Normal Baru - Maun, Maria Redempta Tirtanadi; Widana, Ida Bagus Gede Agung; Susianti, Woro (Journal of Applied Science in Tourism Destination, 2023)
Labuan Bajo is the capital of West Manggarai Regency, East Nusa Tenggara Province and known as one of the 5 priority destinations in Indonesia because it has a variety of natural tourism potential that is still very well preserved. One of the most popular to date is the Komodo dragon, the largest reptile in the world, which can be encountered located in the Komodo National Park area. Seeing the phenomenon that has occurred, the desire for tourists to travel is very high because they are bored for three months experiencing the quarantine period required by the government. Based on the distribution of 216 respondents who travelled to the Komodo National Park area, it was found that there were 5 new factors forming the driving factor, namely Vacation, Escape, Romance, Social Interaction and Relaxation. For the pull factor, 3 new factors are formed, namely Service, Location and Price. While based on the value of the highest loading factor, the most affecting domestic tourists visiting the KNP area are influenced by the Vacation Factor and the Service Factor.